Performance and Post-Harvest Evaluation of Sweet Pepper Genotypes - Rawal, Ranjana; Bhusal, Bikash; Poudel, Sujata; Gautam, Ishwori Prasad (Nepalese Horticulture, 2024)
The study evaluated the novel six open-pollinated sweet pepper genotypes for yield, quality, and self-life at Khumaltar conditions during 2078–2079. The experiment was laid out in RCB design with six treatments and four replications. Each plot was mulched with 25-micron plastic, and 43-day-old seedlings were planted by making a hole at a distance of 60 cm x 45 cm. The result showed that sweet pepper genotypes had a significant effect on yield attributing and quality parameters. HRDCAP004 (575.1) and HRDCAP003 (527.9) recorded the highest number of fruits per plot. However, the highest yield was recorded in genotype HRDCAP001 (37.8 t/ha). The lower yield in genotype ‘HRDCAP003’ (24.7 t/ha), even though it had the highest number of fruits per plot, was due to the smaller fruit size of this genotype. There was a significant effect of the sweet pepper genotype on the quality attributing characters. The content of titratable acidity (0.6 %), Ascorbic acid content (21.1 mg/100g), and fruit firmness (4.1 kg/cm2) was found to be significantly higher in ‘HRDCAP001’ compared to other genotypes. In addition, fruits were wrapped in 25 μ low-density polyethylene bags and stored under Coolbot conditions at 8 oC and 95% relative humidity. The result indicates a significant effect of packaging and storage conditions on the storage life of the tested genotypes. Hence, the genotype HRDCAP001 will be further recommended for farmers’ field trials and a variety registration processes.